Μια νέα ερμηνεία ενός γκράφιτι από υστερορωμαϊκή οικία της αρχαίας Ελεύθερνας - Δεληγιαννάκης, Γεώργιος (Tekmeria, 2024)
P. Themelis (Κριτική Εστία 5, [1994-1996], 269; SEG 45, 1266) published a short graffito that was engraved on the door lintel connecting the rooms 23 and 26 of the so-called House 2 of Sector I of ancient Eleftherna. It reads Νείκην τῷ Κυρείῳ. It has been dated to the third or the early fourth century CE and it has been interpreted as a wish to the God by Christians, possibly related to the religious persecutions of the Roman State against them ca. 250 CE. The use of the terms κύριος and ν(ε)ίκη in Roman and Late Roman acclamations found in textual sources, in both religious and secular contexts, is here analysed; the author rejects the previous interpretations and argues that this graffito is an acclamatory wish for a victory and/or the well-being of the owner of the house. Based on Amm. Marc. 16.8.9, he, moreover, connects it with a contemporary ritual of the Roman house.